2017
DOI: 10.5152/iao.2017.3483
|View full text |Cite
|
Sign up to set email alerts
|

Selective Window Application of Gentamicin Dexamethasone in Meniere's Disease

Abstract: OBJECTIVE:The purpose of the study is to prevent hearing loss when using intratympanic (IT) gentamicin for intractable Meniere's disease. MATERIALS and METHODS:It is a retrospective case review study. Twenty five patients who had definite Meniere's disease and had either selective window application or weekly IT gentamicin were included into the study. First group (selective) had dexamethasone on the round window and gentamicin on oval window during exploratory tympanotomy procedure. The second group had IT ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…Ardıç and colleagues compared the efficacy for 25 patients with MD between dexamethasone combined with gentamicin and gentamicin alone. Their results showed that patients treated with gentamicin alone had severe high-frequency hearing loss, while patients treated with dexamethasone and gentamicin had protected auditory and vestibular cells ( 22 ), further confirming our conclusions.…”
Section: Discussionsupporting
confidence: 86%
“…Ardıç and colleagues compared the efficacy for 25 patients with MD between dexamethasone combined with gentamicin and gentamicin alone. Their results showed that patients treated with gentamicin alone had severe high-frequency hearing loss, while patients treated with dexamethasone and gentamicin had protected auditory and vestibular cells ( 22 ), further confirming our conclusions.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, we considered the risk of ototoxicity to be extremely low. Substances such as CM and antibiotics can pass through the round window membrane (19)(20)(21) and the oval window membrane (20,22,23), but also diffuse into the labyrinth from the blood stream (20,22). We chose iodixanol (Visipaue TM ) as the CM, both in our animal study (13) and in this human study, due to its properties.…”
Section: Discussionmentioning
confidence: 99%